2013
DOI: 10.1177/1933719113488452
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Placental Protein 14 in the Pathogenesis of Endometriosis

Abstract: Placental protein 14 (PP-14) is the principal secretory phase product of endometrium and has been shown to inhibit cell immune function. But its role in the pathogenesis of endometriosis is controversy. The objective of this study is to determine the concentrations of PP-14 in peritoneal fluid (PF) and serum and PP-14 protein expression in endometriotic lesions in women with ovarian endometriosis (n ¼ 75) when compared to women without endometriosis (n ¼ 49) between day 7 and day 20 of their menstrual cycle. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…29 Glycodelin-A has also been proposed as a potential biomarker of endometriosis; indeed several studies reported an increase in GdA concentration in serum and peritoneal fluid of women affected by this pathology. 7,18,30 Moreover, by both immunohistochemistry and microarray analysis, it has been reported a decrease in GdA expression at the window of implantation in eutopic versus healthy endometrium. 5,19 Our results are partially in agreement with these papers since we could confirm, by 2-D electrophoresis and immunofluorescence analysis, a decrease in GdA expression at the window of implantation in eutopic compared to healthy endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…29 Glycodelin-A has also been proposed as a potential biomarker of endometriosis; indeed several studies reported an increase in GdA concentration in serum and peritoneal fluid of women affected by this pathology. 7,18,30 Moreover, by both immunohistochemistry and microarray analysis, it has been reported a decrease in GdA expression at the window of implantation in eutopic versus healthy endometrium. 5,19 Our results are partially in agreement with these papers since we could confirm, by 2-D electrophoresis and immunofluorescence analysis, a decrease in GdA expression at the window of implantation in eutopic compared to healthy endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…The level of FOXA2 protein decreases substantially in the ectopic tissue from patients with endometriosis relative to normal endometrium, which corresponds with the results reported for placenta protein (PP-14) from serum of patients with endometriosis. 51 The staining also reveals that FOXA2 is mainly present in the nucleus of both endometrial glandular and luminal epithelial cells but not in stroma cells. These results confirmed our integrative analysis results, suggesting that FOXA2 and TFAP2C might be implicated in endometriosis.…”
Section: Validation Of Foxa2 and Tfap2c Downregulation In Endometriosismentioning
confidence: 95%
“…Gd-A suppresses the function of T cells and/or NK cells by its direct anti-proliferative and/or pro-apoptotic action on these immune cells [ 29 – 31 , 40 , 41 ]. It has been reported that endometriosis patients had significantly higher serum and peritoneal fluid (PF) concentrations of Gd-A compared with control women without endometriosis and displayed Gd-A expression in endometriosis lesions [ 43 , 44 ]. All these findings indicate that Gd-A exhibits a potential role in creating an immunosuppressive environment in pelvis and in the pathogenesis of endometriosis.…”
Section: Discussionmentioning
confidence: 99%